Clinical and Laboratory Follow-up After Hospitalization for COVID-19 at an Italian Tertiary Care Center. (4th February 2021) - Spinicci, Michele; Vellere, Iacopo; Graziani, Lucia; Tilli, Marta; Borchi, Beatrice; Mencarini, Jessica; Campolmi, Irene; Gori, Leonardo; Rasero, Laura; Fattirolli, Francesco; Olivotto, Iacopo; Lavorini, Federico; et al.
Abstract: We evaluated 100 postacute coronavirus disease 2019 (COVID-19) patients a median (interquartile range) of 60 (48–67) days after discharge from the Careggi University Hospital, Italy. Eighty-four (84%) had at least 1 persistent symptom, irrespective of COVID-19 severity. A considerable number of hospital readmissions (10%) and/or infectious diseases (14%) during the postdischarge period were reported.